Euphemism of taboo translation in the Big Little Lies Series - Rita Lestari; Adi Sutrisno (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
To maintain cultural conformity and moral standards and ensure the target language can receive the message. Translators often use translation strategies that replace or disguise taboo words with more neutral and polite expressions to express the same message. Therefore, this study attempts to identify translation strategies and the implications of using those strategies. This study uses a qualitative descriptive method with the data source "Big Little Lies series", taken from the HBO website and translated by Dhani as a free translator. The data is taken only for taboo words that have euphemism meanings in the target language. From the 145 data collected, Mona Baker's 5 strategies were found, namely (1) Omission translation strategy with many as 50 data, (2) Less expressive translation strategy with many as 38 data, (3) Paraphrase translation strategy with related words with many as 29 data, (4) There 23 data are borrowing translation strategies, and (5) 14 data that uses translation strategies using more common words. Using those strategies has implications for reducing the emotional value of the source language, saving the esteem of the viewer, and smoothing the use of taboo words so that their usage can be accepted in the target language's culture.